(untitled) (Verbum. Revista de teologie catolică, 2025)
It is hard to accept, but there are people who are not able to love. They do not love others and they do not love themselves, whether they have lost their self, as in the case of advanced-stage Alzheimer’s patients, or they have a confused or multiple self, as happens to abandoned children with a long history of institutionalization or those suf-fering from reactive attachment disorder. The inability to love throws into sharp relief two dimensions of any kind of love: gratitude and trust. Gratitude not only as an act of emotional restitution in respect of a received gift, but also as an act with a dual identity role: that of preserving the identity of those who no longer know who they used to be and who they are, including in their capacity as lovers and loved ones, while also pre-serving the identity of those who have been taking care of the love journal of which they were a part. And trust, in particular as a response to a child’s trust in the adult on whom they depend.